Is sural flap a reliable option for wound coverage around the ankle? - Mohd Yusof, Nazri; Sulong, Ahmad Fadzli; Sharifudin, Mohd Ariff (2016)
Soft tissue coverage in the distal tibia, heel and ankle remain a challenging issue in orthopaedic surgery. Free flap is considered the best option, however, distally based reverse sural flap seems effective in relatively small wounds or in unfit patients. The ischaemic complications for sural flap could reach 36%, therefore, a two stage procedure was introduced. Improved outcome has been attributed to the choke vessels opening up, in which they form communicating vessels between the adjacent perforators and the angiosome territory. Following a review of our practice, we began performing a delayed (2 stage) procedure for patients with comorbidities or large wounds distal to the ankle with no ischaemic complications.